Analysis of Internal Control of the Accounts Receivable System at Sekolah Tinggi Ilmu Administrasi Mandala Indonesia (STIAMI) - Andrayanti, Iin (Technium Social Sciences Journal, 2021)
Accounts receivable is one of the great assets of current assets. Internal control is one way to anticipate the risk of fraud and to avoid negative that can arise due accounts. Internal control system has many elements that need to be designed, the system of separation of powers and separation of responsibilities - especially on the function and operation of the storage accounting functions in order to provide sufficient protection against the wealth, income and corporate accounts. This study was conducted to determine how the internal control of accounts receivable accounting system, what are the obstacles faced in internal control that is implemented and what is being done to minimize the barriers that exist in Sekolah Tinggi Ilmu Administrasi Mandala Indonesia (STIAMI). This study used the descriptive analytical method, which is to analyse and discuss the issues that will be described, explanation and illustration are arranged in a systematic, objective and relevant based on data collected as a basis for making decisions. Research conducted by the descriptive analytical method to determine the implementation of internal control and accounting system accounts. In order to get the information directly from the parties concerned, the researchers conducted in depth interviews with the Board of Management of STIAMI. Based on the results of the research, internal control of accounting systems applied by STIAMI receivables quite effective, it is characterized by the independence of the audit committee or internal watchdog unit which are directly under the auspices of the chairman STIAMI. In addition, management has also implemented STIAMI basic concepts and principles of internal control.